Non-invasive Multimodality Cardiovascular Imaging of the Right Heart and Pulmonary Circulation in Pulmonary Hypertension - Hur, David J.; Sugeng, Lissa (Frontiers in Cardiovascular Medicine, 2019)
Pulmonary hypertension (PH) is defined as resting mean pulmonary arterial pressure (mPAP) ≥25 millimeters of mercury (mmHg) via right heart (RH) catheterization (RHC), where increased afterload in the pulmonary arterial vasculature leads to alterations in RH structure and function. Mortality rates have remained high despite therapy, however non-invasive imaging holds the potential to expedite diagnosis and lead to earlier initiation of treatment, with the hope of improving prognosis. While historically the right ventricle (RV) had been considered a passive chamber with minimal role in the overall function of the heart, in recent years in the evaluation of PH and RH failure the anatomical and functional assessment of the RV has received increased attention regarding its performance and its relationship to other structures in the RH-pulmonary circulation. Today, the RV is the key determinant of patient survival. This review provides an overview and summary of non-invasive imaging methods to assess RV structure, function, flow, and tissue characterization in the setting of imaging’s contribution to the diagnostic, severity stratification, prognostic risk, response of treatment management, and disease surveillance implications of PH’s impact on RH dysfunction and clinical RH failure.